DEVELOPMENT AND QUALITY VALIDATION OF A WEB-BASED GOODS ORDERING SYSTEM FOR SMALL AND MEDIUM ENTERPRISES USING AGILE METHOD AND ISO/IEC 25010 (Department of Informatics Engineering, Faculty of Science and Technology, Universitas Islam Negeri Alauddin, Makassar, Indonesia, 2026)
Digital transformation in Small and Medium Enterprises (SMEs) requires integrated transaction management systems supported by measurable software quality standards. Manual goods ordering processes in SME operations frequently cause data inconsistencies, calculation errors, and reporting delays. This study aims to develop a web-based goods ordering information system for SME practitioners using a sprint-based Agile methodology and to conduct a quality validation based on the ISO/IEC 25010 model. The system was developed through four iterative sprint cycles over eight weeks with continuous stakeholder feedback. Software quality evaluation covered all eight ISO/IEC 25010 characteristics using measurable instruments. Functional testing across 40 scenarios achieved a 95% success rate. Usability was assessed using the System Usability Scale (SUS) with 30 respondents, yielding a score of 82.3 (Excellent category). Performance efficiency testing showed an average response time below two seconds under up to 50 concurrent users. This study is limited to testing within a controlled local server environment and portability evaluation restricted to two operating systems. The results conclude that integrating Agile development with ISO/IEC 25010 evaluation produces an information system that meets the technical specifications and operational requirements to support digital transaction management in the SME sector.